Multi-Disciplinary Management and Surgical Resection of Intracardiac Fibromas Causing Bilateral Ventricular Outflow Tract Obstructions in an Infant. (December 2022) - Stone, Matthew L.; Albertz, Megan L.; Galambos, Csaba; Twite, Mark D.; Campbell, David N.; Di Maria, Michael; Fonseca, Brian; Miyamoto, Shelley D.; Ing, Richard J.
Cardiac tumors remain rare in children with benign pathologies predominating. Indications for surgical management often result from compromised ventricular chamber size, biventricular outflow tract obstruction, impaired ventricular function, or the presence of medically refractory dysrhythmias. We present a case of a six-month-old infant with two intracardiac fibromas originating in the interventricular septum. The fibromas were causing significant biventricular outflow obstruction. The patient successfully underwent tumor resection on cardiopulmonary bypass The literature on pediatric cardiac tumors is reviewed. Multi-disciplinary medical planning is necessary for successful anesthetic and surgical treatment of this high-risk patient population.